Major element glass geochemistry data of cryptotephra from Baltic Sea sediment cores EMB201/13-4 and POS507/29-2 measured with an electron micro probe analyser (EMPA) - Müller, Daniela J M; Neugebauer, Ina; Kearney, Rebecca J; Schwab, Markus J; Appelt, Oona; Czymzik, Markus; Kaiser, Jérôme; Arz, Helge Wolfgang; Brauer, Achim (In: Müller, DJM et al. (2025): Major element geochemistry of tephra glass shards and age model construction in Baltic Sea sediment cores EMB201/13-4 and POS507/29-2 [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.984844 (DOI registration in progress), 2025)
This dataset provides the first tephra results from Baltic Sea sediments, analyzed in sediment cores EMB201/13-4 and POS507/29-2 from the Western Gotland Basin. Using chronostratigraphic information from previous Western Gotland Basin age models, both cores were scanned selectively to target specific large Holocene volcanic eruptions in Iceland. Core EMB201/13-4 was analyzed between 220-270 cm, 316-322 cm, and 350-400 cm; core POS507/29-2 between 0-55 cm. Sampling for cryptotephra was performed first in continuous 5-cm steps and subsequently in contiguous 1-cm steps after tephra identification in the 5-cm samples. The central part of EMB201/13-4 was only sampled in continuous 1-cm steps. In total, 62 samples were investigated. The cryptotephra glass shard extraction protocol followed established separation procedures after Blockley et al. (2005). Glass shards were identified, counted and picked in water under a Keyence VHX-970F digital microscope using a Keyence VH-Z100R lens and the VHX Control System (Kearney et al. 2024), as well as using a 100 μm-diameter gas-chromatography syringe attached to a micromanipulator (Lane et al. 2014, doi:10.1016/j.jas.2013.10.033). Subsequently, the shards were embedded in Araldite 2020 epoxy resin, and ground and polished for electron probe microanalyses (EPMA). Major element composition of individual glass shards was measured using a JEOL JXA-8230 electron microprobe at GFZ Potsdam, Germany (15 kV, 10 nA, 5-10 µm beam size). Instrumental calibration used natural mineral standards and analytical runs were monitored using glass standards (see dataset "Electron micro probe analyser (EMPA) glass standard measurements associated with glass geochemistry data of cryptotephra from cores EMB201/13-4 and POS507/29-2"). Sample measurements with analytical totals below 95% were excluded, so that 132 volcanic glass shards in 21 samples remain in total. In core EMB201/13-4, four peaks in glass shards were identified as tephra horizons in the time interval 4500-2000 a BP, with isochrons within these horizons being defined as first major occurrence of glass shards. The glass measurements show mostly rhyolitic, dacitic and andesitic compositions and only minor contributions from basaltic and phonolitic glasses, clustering in five tephra populations and 32 geochemically different shards. The majority of shards is sourced from Icelandic volcanoes.
Keywords: Age model; Baltic Sea; Cryptotephra; marine reservoir age; Marine Sediment Core; Radiocarbon ages; tephrochronology; Western Gotland Basin